Housing, street and health: a new systemic research framework - Anna Pagani; Derek Christie; Valentin Bourdon; Catarina Wall Gago; Stéphane Joost; Dusan Licina; Mathias Lerch; Céline Rozenblat; Idris Guessous; Paola Viganò (Buildings & Cities, 2023)
As the world’s population grows in cities, urban dwellers spend a large amount of time inside their home, making housing health ever more important. Critical for residents’ health, the interactions between indoor residential environments and outdoor environmental conditions (e.g. air pollution, noise, heat) are mediated by the controversial and evolving relationship between housing and the street. Currently, there is a lack of ways to integrate and explore synergies among the plurality of perspectives that have addressed the interactions between housing, street and health (HSH). This paper proposes a systemic research framework to address conceptually, spatially and temporally HSH interactions. With a focus on European cities, determinants of housing health are identified through six perspectives, comprising environmental health, domestic architecture, building technologies, socio-economic inequalities, housing prices and urban planning. Their interrelationships are organised in a causal loop diagram, which can be used to highlight gaps in research and data. Subsequently, the paper explores the research and practical applications of the resulting systemic understanding, taking the context of Geneva, Switzerland, as an example. In sum, this study illustrates ways to integrate systemic, transdisciplinary and spatiotemporal approaches essential to holistically address the complexity of HSH relationships. Practice relevance The interactions between housing, street and health (HSH) have been approached from different and often siloed perspectives, addressing issues ranging from diseases to architectural design and history, building technologies, socio-economic inequalities, housing prices and urban planning. This fragmentation hinders the coordination of interventions aimed at improving the health of residential environments, limiting the identification of synergies and trade-offs. This paper proposes a research framework enabling the integration of knowledge on the HSH interactions. The resulting holistic and systemic understanding is instrumental in fostering collaborations across disciplinary fields and among a variety of stakeholders, in raising awareness of the risks and opportunities associated with HSH interactions, and in supporting the design and implementation of health and wellbeing agendas at the building, neighbourhood or city level.